BEING A TEACHER IS MORE THAN A PROFESSION: REFLECTIONS ON THE TEACHING VOCATION IN THE XXI CENTURY (Annual of the Faculty of Philosophy in Skopje, 2024)
This paper analyzes the position of the teaching profession within the broadersocial reality in the 21st century, with particular reference to the contemporary Macedonianpedagogical and social context. The paper first gives a summary presentation ofseveral central points related to the teaching profession in modern society: 1. Interpretationof this year’s UNESCO theme: “The Transformation of Education Begins withTeachers”; 2. Consulting several theories that give a broader perspective to the teachingprofession in general (Konrad Liessmann, George Steiner, John Dewey and JeromeBrunner); 3. Criticism of the negative tendency to interpret the teaching profession fromthe point of view of information transmission, and not within the broader educationalprocess, as the theory and history of pedagogy dictates. The rest of the paper deals withthe application of general pedagogical and philosophical theories to the contemporaryMacedonian contest in dialogue with the specific Macedonian pedagogical tradition.The paper pays particular attention to the “Conception of Primary Education” (2021),which is interpreted as an attempt to reinterpret and rehabilitate the position of theteacher in contemporary Macedonian education.
Keywords: education; teacher; competencies